Description of the consumption of toxics in patients with assertive community treatment and prolonged release treatment. (13th April 2021) - Garcia, L.; Rodriguez, C.; Willems, A.I.
Abstract : Introduction: The Assertive Community Treatment (ACT) was developed by Leonard Stein and Mary Ann. The objective is the treatment of serious Mental Disorders in an integral way and in the community. Objectives: The Assertive Community Treatment (ACT) was developed by Leonard Stein and Mary Ann. The objective is the treatment of serious Mental Disorders in an integral way and in the community. Methods: This is a retrospective study with a total of 69 patients whose main diagnosis is Schizophrenia undergoing CT follow-up in 2018-2019. The data obtained have been analyzed by the SPSS statistical program. Results: Our sample is mainly composed of men (60.9%) with an average age of 48 years (+ - 11.56). The main diagnosis is schizophrenia (62.3%) and the most commonly used long-term injectable treatment is paliperidone palmitate with a dose range of 150mg. Of the total number of patients, 29% of the cases did not maintain active use of any toxic, and the most commonly used toxic is tobacco (49.3% of cases). Conclusions: The inclusion of patients in a ACT program requires a diagnosis of severe Mental Disorder and poor therapeutic adherence. After analyzing our data, we observed that most of them also have active toxic consumption and high doses of psychotropic drugs. Disclosure: No significant relationships.